Iglesia y sociedad en el Cádiz del siglo XVIII / Arturo Morgado García ; prólogo de Antonio Domínguez Ortiz - Domínguez Ortiz, Antonio (1909-2003); Morgado García, Arturo
Fuentes y bibliografía: p. 277-283